1997
DOI: 10.1111/j.1751-1097.1997.tb01915.x
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of Hypocrellin B and Hypocrellin B Derivatives as Sensitizers for Photodynamic Therapy of Cancer: Progress Update

Abstract: Hypocrellins are perylenequinone pigments with substantial absorption in the red spectral region and high singlet oxygen yield. They are available in pure monomeric form and may be derivatized to optimize properties of red light absorption, tissue biodistribution and toxicity. In vitro screening of synthetic derivatives of the naturally occurring compound, hypocrellin B (HB), for optimal properties of cyto-(dark) toxicity and phototoxicity resulted in selection of three compounds for preclinical evaluation: HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 27 publications
(9 reference statements)
0
46
0
1
Order By: Relevance
“…Indeed, the sensitivity of these organelles to photosensitization has previously been reported for other photosensitizers [e.g. hypocrellin B (Miller et al 1997) and its derivatives (Uzdensky et al 2001), hypericin (Siboni et al 2002), toluidine blue (Trembaly et al 2002), temoporWn (Teiten et al 2003)]. The possible role of the ER or the endosome-Golgi compartment in cell death induction through photodamage is supported by the observation that stresses applied to these structures may trigger the apoptotic cascade via the activation of either regulatory proteins or directly acting apoptotic proteases, such as caspase 12 or caspase 2 (Ferri and Kroemer 2001;Boyce and Yuan 2006;Kessel et al 2006;Nakagawa et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, the sensitivity of these organelles to photosensitization has previously been reported for other photosensitizers [e.g. hypocrellin B (Miller et al 1997) and its derivatives (Uzdensky et al 2001), hypericin (Siboni et al 2002), toluidine blue (Trembaly et al 2002), temoporWn (Teiten et al 2003)]. The possible role of the ER or the endosome-Golgi compartment in cell death induction through photodamage is supported by the observation that stresses applied to these structures may trigger the apoptotic cascade via the activation of either regulatory proteins or directly acting apoptotic proteases, such as caspase 12 or caspase 2 (Ferri and Kroemer 2001;Boyce and Yuan 2006;Kessel et al 2006;Nakagawa et al 2000).…”
Section: Discussionmentioning
confidence: 95%
“…These pigments have a long history of use as traditional medicinal agents and were commonly used to treat rheumatoid arthritis, gastric diseases (20), and skin diseases related to fungal infections (18,19). Previous studies showed that hypocrellins exhibited photodynamic anticancer (2,5,12,21) and antiviral (9, 10) activities. These activities were related to their ability to generate active oxygen…”
mentioning
confidence: 99%
“…As a type of photosensitizer, hypocrellin A (HA), a naturally occurred hydrophobic perylenequinonoid pigments isolated from Hypocrella bambusae, possesses a broad visible absorbance and a high efficiency in generating reactive oxygen species (ROSs) (Miller et al 1997). All these properties make the newly developed photosensitizer present strong photodynamic activity against many tumor cell lines and viruses (Diwu and Lown 1990;Petrich 2000;Hudson et al 1997).…”
Section: Introductionmentioning
confidence: 99%